Type 2 Diabetes and ADP Receptor Blocker Therapy - Matej Samoš; Marián Fedor; František Kovář; Michal Mokáň; Tomáš Bolek; Peter Galajda; Peter Kubisz; Marián Mokáň (Journal of Diabetes Research)
Type 2 diabetes (T2D) is associated with several abnormalities in haemostasis predisposing to thrombosis. Moreover, T2D was recently connected with a failure in antiplatelet response to clopidogrel, the most commonly used ADP receptor blocker in clinical practice. Clopidogrel high on-treatment platelet reactivity (HTPR) was repeatedly associated with the risk of ischemic adverse events. Patients with T2D show significantly higher residual platelet reactivity on ADP receptor blocker therapy and are more frequently represented in the group of patients with HTPR. This paper reviews the current knowledge about possible interactions between T2D and ADP receptor blocker therapy.